THE MANAGEMENT OF INDEPENDENT CURRICULUM IMPLEMENTATION: A MULTI-SITE STUDY AT SMA NEGERI 3 AND SMA NEGERI 7 BANJARMASIN - Rahmiani, Risna; Suriansyah, Ahmad; Suhaimi, Suhaimi (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to describe the management of the implementation of the Independent Curriculum (Kurikulum Merdeka) at two senior high schools-SMA Negeri 3 and SMA Negeri 7 Banjarmasin-by focusing on three main aspects: implementation readiness, principal strategies, and efforts to develop teacher professionalism. The research employed a qualitative approach with a multi-site study design. Data were collected through observation, in-depth interviews, and documentation, and then analyzed both individually (per site) and across sites. The findings reveal that both schools have demonstrated readiness in developing school-based curricula, preparing teaching modules, and designing learning tools aligned with student characteristics. SMA Negeri 3 emphasizes internal development based on input from the school community, while SMA Negeri 7 refers more to guidelines from the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). The principals' strategies in implementing the Independent Curriculum include supervision, coaching, reflection, and providing feedback. At SMA Negeri 3, the approach is more collaborative and participatory, involving parents and the wider community, whereas SMA Negeri 7 adopts a more systematic and structured approach. In terms of developing teacher professionalism, both schools conduct training, support certification upgrades, and utilize digital learning platforms. Cross-site findings show that differences in managerial strategies lead to variations in curriculum implementation; however, both schools face similar challenges in the areas of evaluation and ongoing monitoring. This study recommends strengthening the evaluation system and providing more context-based teacher training to ensure that the implementation of the Independent Curriculum is optimal and sustainable